Study on Alloy Steel TEW 6582 Machined Surface Rougness Under Dry Machining - Napid, Suhardi; Rafiq Yanhar, Muhammad; Bakhori, Ahmad; Hasibuan, Abdurrozzaq; Krianto Sulaiman, Oris; Asaad, Mhd. (International Journal of Engineering and Technology, 2018)
The purpose of research is to study the surface roughness of machining results obtained to give consideration that the possibility of dry machining can be realized at alloy steel machining of TEW 6582. In the field of surface texture only discuss the machined surface roughness with some testing that is processing and data analysis can be done statistically. The TEW 6582 alloy steel samples were produced from dry machining operations with 9 cutting forms using standard L 9 (34). In this case 3 variations of tool wear are determined by tool edge wear (VB) = 0.1 mm, 0.3 mm and 0.6 mm including also in wet machining. To cut the work piece used CNC machine, optical microscope and surface test . The roughness test was obtained the roughness value with dry machining for optimum cutting conditions ie HPK1.0.1 = 1,467 μm, HPK8,0.3  = 2,133 μm and HPK8,0.6 = 2,8 μm whereas value in wet machining was found with HPB1,0.1 = 1,581 μm, HPB8.0.3 = 2,304 μm and HPB8,0.6 = 2,906 μm. From the above machining results data, HPK8.06 can be determined as the most optimum cutting condition which can be concluded that dry machining gives better machining results  roughness through Ravg value and no significant difference is obtained when compared to wet machining after statistically analyzed, so that dry machining is a good chance that can be realized in manufacturing and automotive industries.